John Steinbeck : The Years of Greatness, 1936-1939 - Hayashi, Tetsumaro (Book collections on Project MUSE., 1993)
This volume is derived from papers presented by the North American delegates at the Third International Steinbeck Congress, held in May 1990 in Honolulu, Hawaii, under the co-sponsorship of the Steinbeck Society of Japan and the International Steinbeck Society. These ten essays, arranged in two parts, seek to provide a clearer understanding of Steinbeck's life and work during his most productive period. Part I discusses Steinbeck's women, with emphasis on the function of the feminine from original perspectives. It uses recent research sources, including some of the Steinbeck-Gwyn love letters.